2019
DOI: 10.1155/2019/5219782
|View full text |Cite
|
Sign up to set email alerts
|

miR-29a Negatively Affects Glucose-Stimulated Insulin Secretion and MIN6 Cell Proliferation via Cdc42/β-Catenin Signaling

Abstract: Background Diabetes is a progressive metabolic disease characterized by hyperglycemia. Functional impairment of islet β cells can occur to varying degrees. This impairment can initially be compensated for by proliferation and metabolic changes of β cells. Cell division control protein 42 (Cdc42) and the microRNA (miRNA) miR-29 have important roles in β-cell proliferation and glucose-stimulated insulin secretion (GSIS), which we further explored using the mouse insulinoma cell line MIN6. Methods Upregulation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 59 publications
3
19
0
Order By: Relevance
“…MiR-29a is a well-established regulator of insulin secretion and beta cell function (Bagge et al 2012 ; Dooley et al 2016 ; Pullen et al 2011 ; Duan et al . 2019 ) and therefore an exciting candidate to investigate further. Approximately, 33% of the GPS genes after iAs III exposure harbor predicted miR-29a target sites, and nearly 25% of the GPS genes after MAs III exposure are also predicted to be targeted by miR-29a (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MiR-29a is a well-established regulator of insulin secretion and beta cell function (Bagge et al 2012 ; Dooley et al 2016 ; Pullen et al 2011 ; Duan et al . 2019 ) and therefore an exciting candidate to investigate further. Approximately, 33% of the GPS genes after iAs III exposure harbor predicted miR-29a target sites, and nearly 25% of the GPS genes after MAs III exposure are also predicted to be targeted by miR-29a (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…MiR-29a is a well-established modulator of insulin secretion, in part through regulation of target genes such as syntaxin-1 (Bagge et al 2012 ; Pullen et al 2011 ; Duan et al . 2019 ; Filios and Shalev 2015 ; Baran-Gale et al . 2013 ; Bagge et al 2012 ; Roggli et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, four of the five miRNAs that were significantly increased during the second visit (24–28 weeks of gestation), miR-29a, miR-134-5p, miR-433-3p and miR-330-3p, are involved in pancreatic beta cell function [ 9 , 43 , 44 , 45 , 46 , 47 ]. MiR-29a, which increased with increasing glucose concentrations, impairs glucose-stimulated insulin secretion at least partially via targeting the exocytosis protein Syntaxin 1 [ 43 , 44 , 45 ], while miR-330-3p targets glucokinase, the gene responsible for Maturity Onset Diabetes of the Young, subtype 2 (MODY2). Both miR-134-5p and miR-433-3p belong to a microRNA cluster (C14MC) within the imprinted DLK1-DIO3 locus on chromosome 14.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, one study demonstrated that miR-29a inhibits glucose-stimulated insulin secretion (GSIS) and cell proliferation in MIN6 cells via a negative effect on Cdc42/β-Catenin signaling [31]. It has also been suggested that miR-29a inhibits GSIS by targeting syntaxin-1 and Mct1, as well as insulin signaling by targeting INSIG1, CAV2, PIK3R1 [32,33].…”
Section: Discussionmentioning
confidence: 99%